PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA BERBAGAI PERBANDINGAN MEDIA TANAM SOLID DECANTER DAN TANDAN KOSONG KELAPA SAWIT PADA SISTEM SINGLE STAGE - Syukri Habibi Nasution; Chairani Hanum; Jasmani Ginting (Universitas Sumatera Utara, 2014)
The objective of this research to study the best composition of various comparison of media soliddecanter and oil palm empty fruit bunch. This research was conducted at Kebun Bangun PTPN IIIKabupaten Simalungun, Pematang Siantar with a height of ± 300 metres above sea level, beginNovember 2012 until July 2013 by using a Randomized Block Design Non Factorial with 11treatment of growing media. The results showed that treatment of growing media significantlyaffected all parameters except plant heigt 6, 8, and 10 week after plan. Using oil palm empty fruitbunch on planting medium increased shoot root ratio.Keywords :solid decanter, palm oil empty fruit bunches, palm oil